Workshop on Designing Poster for Preservice Tour Guides in North Toraja, South Sulawesi - Nawir, Muhammad Syahruddin; Maqfira, Nur; Premitri, Novia; Rahayu, Andini; Wardana, Rifka; Achmad, Nurul Masita (IJOCSE: Indonesian Journal of Community Services, 2023)
Workshops are practical activities that focus on observing the relationship between training and its forms and results. The activity focused on designing posters for cultural introduction in the North Toraja area, especially Bori’ Kalimburan and Kete’ Kesu. This workshop activity is expected to increase knowledge, attitudes, and skills, especially in designing tourist posters that can be used for promotion and tour guides. The method of this workshop activity is preparation and Implementation. The result of the preparation took over the part of preparing materials, determining the time and place, and establishing the committee. The result of the Implementation part, namely pre-training, submission materials, direct practice, and presentation.